Growth, feed intake, survival, and histological response of white shrimp Litopenaeus vannamei fed diets containing grains naturally contaminated with aflatoxin = Crecimiento, consumo de alimento, supervivencia y respuesta histológica del camarón blanco Litopenaeus vannamei alimentado con dietas de granos contaminados naturalmente con aflatoxinas - Tapia Salazar, Mireya; García Pérez, Oscar Daniel; Velasquez Soto, Ruth Abigail; Nieto López, Martha Guadalupe; Villarreal Cavazos, David Alonso; Ricque Marie, Denis; Cruz Suárez, Lucía Elizabeth (Universidad Autónoma de Baja California, Instituto de Investigaciones Oceanológicas, 2012)
Two feeding trials were carried out to evaluate the effect of diets containing corn or peanut grains naturally contaminated with aflatoxins on the growth, feed intake, survival, and histological response of the white shrimp Litopenaeus vannamei. In trial 1, four experimental diets were formulated to contain 0, 500, 1000, and 2000 g kg–1 of total aflatoxins (TA) and fed to L. vannamei juveniles for 28 days. In trial 2, six experimental diets were formulated to contain 0, 10, 20, 40, 60, and 120 g kg–1 TA and fed to L. vannamei juveniles for 64 days. Feed intake and weight gain were significantly affected by the presence of aflatoxins from naturally contaminated grains. Feed conversion rate increased significantly from a level of inclusion of 60 g kg–1. Survival was significantly reduced only for shrimp fed diets supplemented with 1000 and 2000 g kg–1 TA. Shrimp exposed to higher aflatoxin inclusion levels presented significantly lower lipid vacuole levels in R-cells (12–28%), lower B-cell activity, and lower mitotic E-cell activity. Tubular epithelial atrophy increased from the inclusion level of 20 g kg–1. Hepatopancreatocyte sloughing was significantly higher in shrimp fed diets supplemented with 1000 and 2000 g kg–1 TA. It is worth noting that shrimp fed 40 g kg–1 TA presented a high hepatopancreatocyte sloughing coefficient. Based on these results we conclude that the presence of aflatoxins, even at low levels, reduces feed intake and weight gain, and alters the cells of the hepatopancreas.